The effectiveness of injury prevention programs for youth and adolescent athletes - Weber, M. L.; Lam, K. C.; Valovich McLeod, T. C. (International Journal of Athletic Therapy & Training, 2016)
Clinical Question: In youth and adolescent athletes, are jumping/plyometric exercises more effective than balance exercises in preventing sport-related injuries?